A Magical Journey Through Brazilian Biomes with Customized Artificial Intelligence - Marques, Leonardo G.; Lira, João Vitor V.; Martins, Eduardo Miyake D.; Luz Junior, Jonas de Araújo; Rodrigues, Maria Andréia Formico (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2025)
Introduction: Claws of Fate is a 2D adventure game for players with prior experience in reflex-based platformers, offering a guided and accessible experience. Set in Brazilian biomes such as the Amazon Rainforest and Caatinga, it follows a guardian whose cat escapes through magical portals. The journey to regain the animal’s trust introduces themes like animal welfare, ethical pet care, and environmental conservation as aspects of collective health. Objective: This work presents a game designed to raise awareness of the connections between human behavior, animal wellbeing, and ecosystem preservation. Through a simple narrative and ageappropriate challenges, it supports health education and ethical reflection in early adolescence. Methodology: The game features an AI-based guide that provides real-time text and audio instructions, offering a safe and engaging experience tailored to players. Usability tests were conducted with young adults acting as proxies to assess interface clarity, narrative coherence, and technical performance, focusing on playability and responsiveness. Results: The game aims to contribute to health education by fostering empathy, responsible pet care, and environmental awareness. Its combination of accessible gameplay and AI guidance offers a developmentally appropriate way to explore humananimal relationships and collective health.